(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Recruiting, the most important function of HR is changing its colour. Environmental sustainability & social responsibility has undoubtedly risen to the forefront of discussion. An emerging trend in recruitment is that organizations are looking for candidates with the environment-friendly bent of mind. Also, the younger generation is becoming more and more concerned about the environment and its protection. Young job seekers are savvy, smart, energy driven and wear social & environmental issues up their sleeves. The concept is not very popular; it is slowly catching up with organizations i.e. Green Recruiting. It is an innovative idea through which companies emphasize environmental protection and concern as an important strategy for recruitment. Green Recruitment means a paper-free recruitment process with a minimal environmental impact. It is sharing of the companys unswerving commitment towards the cause of environment with the candidates whom they are trying to hire. In this paper concept, importance, steps, and other areas related to green recruiting have been discussed